uPAR expression in canine normal prostate and with proliferative disorders - Faleiro, Mariana Rodrigues; Toledo, Denise Caroline; Rodrigues, Marcela Marcondes Pinto [UNESP]; Amorim, Renée Laufer [UNESP]; Brito, Luiz Augusto Batista; Damasceno, Adilson Donizeti; Moura, Veridiana Maria Brianezi Dignani de (Universidade Federal de Goiás, 2013)
Prostatic lesions such as prostatic intraepithelial neoplasia (PIN) and proliferative inflammatory atrophy (PIA) are studied in human and canine species due to their malignance potential. The plasminogen activator (PA) system has been suggested to play a central role in cell adhesion, angiogenesis, inflammation, and tumor invasion. The urokinase-type plasminogen activator receptor (uPAR) is a component of the PA, with a range of expression in tumor and stromal cells. In this study, uPAR expression in both canine normal prostates and with proliferative disorders (benign prostatic hyperplasia-BPH, proliferative inflammatory atrophy-PIA, prostatic intraepithelial neoplasia-PIN, and carcinoma-PC) was evaluated by immunohistochemistry in a tissue microarray (TMA) slide to establish the role of this enzyme in extracellular matrix (ECM) remodeling and in the processes of tissue invasion. A total of 298 cores and 355 diagnoses were obtained, with 36 (10.1%) normal prostates, 46 (13.0%) with BPH, 128 (36.1%) with PIA, 74 (20.8%) with PIN and 71 (20.0%) with PC. There is variation in the expression of uPAR in canine prostate according to the lesion, with lower expression in normal tissue and with BPH, and higher expression in tissue with PIA, PIN and PC. The high expression of uPAR in inflammatory and neoplastic microenvironment indicates increased proteolytic activity in canine prostates with PIA, PIN, and PC.

Lesões prostáticas como a neoplasia intraepitelial prostática (PIN) e a atrofia inflamatória proliferativa (PIA) são estudadas na espécie humana e canina devido ao seu potencial de malignidade. O sistema de ativador de plasminogênio (PA) tem sido sugerido como um importante mecanismo na adesão celular, angiogênese, inflamação e invasão tumoral. O receptor ativador de plasminogênio do tipo uroquinase (uPAR) é um componente do PA, expresso em células tumorais e estromais. Avaliou-se, por imunoistoquímica em lâmina de microarranjo tecidual (TMA), a expressão de uPAR no tecido prostático canino normal e com desordens proliferativas (hiperplasia prostática benigna-HPB, atrofia inflamatória proliferativa-PIA, neoplasia epitelial prostática-PIN e carcinoma-CP), com o objetivo de verificar o papel desta enzima na remodelação de matriz extracelular (ECM) e no processo de invasão tecidual. Foram obtidos 298 cores e 355 diagnósticos, sendo 36 (10,1%) próstatas normais, 46 (13,0%) com HPB, 128 (36,1%) com PIA, 74 (20,8%) com PIN e 71 (20,0%) com CP. Há variação na expressão de uPAR na próstata canina de acordo com a lesão, com menor expressão nas glândulas normais e com HPB, e maior naquelas com lesões displásicas e (PIA e PIN) e neoplásicas (CP). A superexpressão de uPAR nos microambientes inflamatório e neoplásico indica aumento da atividade proteolítica em próstatas caninas com PIA, PIN e CP.
Expressão de uPAR na próstata canina normal e com lesões proliferativas
Keywords: carcinoma prostático; CD87; PIA; PIN; TMA; CD87; PIA; PIN; prostatic carcinoma; TMA